Validation and reliability of a modified sphygmomanometer for the assessment of handgrip strength in Parkinson´s disease - Silva,Soraia M. (2015)
BACKGROUND: Handgrip strength is currently considered a predictor of overall muscle strength and functional capacity. Therefore, it is important to find reliable and affordable instruments for this analysis, such as the modified sphygmomanometer test (MST). OBJECTIVES: To assess the concurrent criterion validity of the MST, to compare the MST with the Jamar dynamometer, and to analyze the reproducibility (i.e. reliability and agreement) of the MST in individuals with Parkinson's disease (PD). METHOD: The authors recruited 50 subjects, 24 with PD (65.5±6.2 years of age) and 26 healthy elderly subjects (63.4±7.2 years of age). The handgrip strength was measured using the Jamar dynamometer and modified sphygmomanometer. The concurrent criterion validity was analyzed using Pearson's correlation coefficient and a simple linear regression test. The reproducibility of the MST was evaluated with the coefficient of intra-class correlation (ICC2,1), the standard error of measurement (SEM), the minimal detectable change (MDC), and the Bland-Altman plot. For all of the analyses, α≤0.05 was considered a risk. RESULTS: There was a significant correlation of moderate magnitude (r≥0.45) between the MST and the Jamar dynamometer. The MST had excellent reliability (ICC2,1≥0.7). The SEM and the MDC were adequate; however, the Bland-Altman plot indicated an unsatisfactory interrater agreement. CONCLUSIONS: The MST exhibited adequate validity and excellent reliability and is, therefore, suitable for monitoring the handgrip strength in PD. However, if the goal is to compare the measurements between examiners, the authors recommend that the data be interpreted with caution.